The anti-cancer effect of interferon induced protein with tetratricopeptide repeats 2 (IFIT2) and HECT and RLD domain containing E3 ubiquitin protein ligase 5 (HERC5) on breast cancer cell lines in the context of cell migration and apoptosis - Bezuidenhout, Ludick Wynand (Stellenbosch : Stellenbosch University, 2025)
Bezuidenhout, L. W. 2025. The anti-cancer effect of interferon induced protein with tetratricopeptide repeats 2 (IFIT2) and HECT and RLD domain containing E3 ubiquitin protein ligase 5 (HERC5) on breast cancer cell lines in the context of cell migration and apoptosis. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/4f171045-c058-445b-a861-4ee27eb04c19